A survey of school-family-community partnerships in Kenya. Issue 4 (16th October 2017) - Nyatuka, Benard Omenge
Abstract : Purpose: The creation of sound school-family-community partnerships is being widely acknowledged as it strengthens school programs, family practices, student learning and behavior, as well as development. Active participation of parents and communities in the school tends to reduce the traditional unidirectional accountability of teachers as a sole party responsible for learners' success. Furthermore, such collaboration is said to cultivate new hope about schools and education, especially among rural communities. However, key stakeholders in education claimed that school-family-community partnerships were weak in primary schools in Kakamega County, Kenya (Ministry of Education (MOE), 2010). The paper aims to discuss these issues. Design/methodology/approach: This study was designed to generate relevant empirical evidence. The study was guided by the Social Capital Theory (Field, 2003; Horvat et al., 2003; Coleman, 1994; Bourdieu and Wacquant, 1992) whose central thesis is that social networks are a valuable asset, as interaction enables people to build communities, commit themselves to each other, and knit the social fabric. Using stratified random sampling, a sample of 361 primary school teachers in 34 schools drawn from a population of 8, 964 teachers in 848 primary schools, cutting across the 12 districts in the county, was involved in the study. A questionnaire was developed and used to collect the teachers' views of school-family-community partnership practices in the schools. The data generated were analyzed and presented by means of such descriptive statistics as frequencies, percentages, and the mean. Findings: The findings revealed gaps with respect to collaboration among schools, families, and the community as the key focus in this study. Results indicated that the school-family-community partnerships in the county remained at a transactional rather than a transformational level. In light of the findings, relevant policy recommendations were proposed to improve practice, with particular attention to providing meaningful professional learning as well as desirable student outcomes. Originality/value: This is one of the largest county-level studies in Kenya directly addressing teacher-family partnerships and illuminating the ways in which schools can build internal capacity for effective family engagement.